The Power of Country of Origin and Brand Love: COSRX Repurchase Intention Journey Update - Laelatul Badriyah; Nurisnaeni Nurisnaeni; H. Misbak; Tiara Muthiarsih (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
Today’s consumer journey needs to be carefully studied by marketers, their ever-changing repeat purchasing behavior requires serious attention from various sides. The Brand they looking for base on more than “Product of View” physically. This research aims to explore the journey of consumers’ repurchase intention in Korean skincare products COSRX through the influence of country of origin and brand love. The method used is quantitative approach with multiple regression, sample is determine from non-probability sampling technique to 260 COSRX consumers of Ciayumajakuning Area – West Java – Indonesia through an online questionnaire survey. The research uses 3 classical assumption tests that are relevant to multiple regression. The results of the study indicate that the journey of consumers repurchase intention in Korean skincare products COSRX is positively and significantly powered partially and simultaneously by country of origin and brand love with a strong category contribution, with the t-table value of 1.969 and the F-table of 404.187. > 3.03. This insight usefully for retailers as well as marketers to keep detail attention of brand not only physically but emotionally.